Exploring the relationship between metal ion valency and electron transfer in copigmentation processes of cyanidin-3-O-glucoside in simulated fruit wine solutions - Bo Zhang; Juan-Di Wu; Qiang Wang; Shu-Yan Wang; Pan-Pan Zhou; Li-Ting Han (Current Research in Food Science)
In this experiment, five metal ions (K+, Mg2+, Al3+, Ga3+, and Sn4+) were utilized as copigments to investigate their copigmentation processes with cyanidin-3-O-glucoside (C3OG) in simulated fruit wine solutions. The color characteristics were analyzed using Glories and CIELAB methods, and the copigmentation effects were determined spectrophotometrically. Thermodynamic parameters, including the equilibrium constant (K) and standard Gibbs free energy (ΔG°), were calculated to comprehend the binding affinity between metal ions and C3OG. Ultra-fast femtosecond spectroscopy was employed to monitor the photoinduced electron transfer process between C3OG and cations. Theoretical calculations were also conducted to support experimental findings. The results revealed that the presence of metal ions significantly enhanced the color intensity of C3OG in simulated fruit wine solutions. Higher valency cations, particularly Sn4+, Ga3+, and Al3+, exhibited superior copigmentation effects, resulting in significant bathochromic and hyperchromic changes. Thermodynamic analysis confirmed that the interaction between C3OG and metal ions was spontaneous and exothermic. Ultra-fast femtosecond spectroscopy demonstrated that electron transfer from C3OG to metal ions occurred, with the efficiency of transfer being dependent on valency. Theoretical calculations corroborated the experimental results by highlighting the role of metal ions in stabilizing C3OG/metal complexes through electron transfer. The findings presented in this study contribute to a more comprehensive understanding of pigment/metal complexes and the underlying chemistry behind fruit wine color. Furthermore, it advances the theoretical foundation of copigmentation and broadens its applications in the beverage industry.